Emergency response implications of tritium in CANDU severe accidents. (1st December 2022) - Lebel, Luke; Brown, Morgan; Vucicevic, Jelena; Korolevych, Volodymyr
Highlights: Consider the implications of tritium releases in CANDU severe accidents. Updated method for calculating tritium accident source term in MAAP-CANDU. Developed simplified environmental transport model for calculating inhalation dose. Tritium dose contribution via inhalation most important during more mild accidents. Shortcomings of intervention levels addressed with new derived air concentration limit. Abstract: Tritium is produced in large quantities by heavy-water moderated CANDU reactors. Even though it is only a weak beta emitter, its dose impact during reactor accidents can be important under certain circumstances. Improved models for characterizing the transport of tritium as part of steam and water have been developed as an external model in the MAAP-CANDU severe accident code. Owing to the high mobility of tritiated steam, a large fraction of the radionuclide inventory can be released to the environment, where its contribution to inhalation doses can be significant. Moreover, after the accident, plant evapotranspiration can lead to continued elevated airborne tritium concentrations in contaminated areas, as shown with a simplified environmental transport model. Gamma measurement-based operational intervention levels (OILs) can miss this contribution, and it is proposed to use derived air concentration limits as an additional metric for making decisions about emergency protective actions like evacuation or relocation.